2022
DOI: 10.3390/min12121549
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Microstructure of Iron Tailings Cemented Paste Backfills Using Carbide Slag-Activated Ground Granulated Blast-Furnace Slag as Alternative Binder

Abstract: For rational disposal of solid wastes, low-cost cemented paste backfills (CPB) were prepared with iron tailings, ground granulated blast-furnace slag (GGBS), and calcium carbide slag (CS). To ensure that CPB can be effectively utilized in mine backfill projects, the effects of solid contents, GGBS content, CS/GGBS ratio, and mixing water on the workability and mechanical properties of CPB were investigated. The results indicated that when the solid content was 70%, the GGBS content was 14%, the CS/GGBS ratio w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…To attain the required mechanical strengths of CTB while maintaining its rheological properties [38], the proportion of each component must be determined [39]. Various extra materials such as sand [40,41], fiber [42,43], and pozzolans [44,45] have been recently used to reduce the backfill costs while increasing its strength behavior. Since ROM ore is also crushed into finer particles to boost ore recovery [46], the tailings employed for CTB making can easily cause low UCS values [47].…”
Section: Introductionmentioning
confidence: 99%
“…To attain the required mechanical strengths of CTB while maintaining its rheological properties [38], the proportion of each component must be determined [39]. Various extra materials such as sand [40,41], fiber [42,43], and pozzolans [44,45] have been recently used to reduce the backfill costs while increasing its strength behavior. Since ROM ore is also crushed into finer particles to boost ore recovery [46], the tailings employed for CTB making can easily cause low UCS values [47].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the addition of straw fiber increased the tensile properties of the CPB, and it was also found that this strengthening effect was weakened when the curing time was increased. The above-mentioned research demonstrated that adding substances to CPB increases its toughness [28][29][30][31][32]. However, to date, there have been few studies on the influence of rubber on the mechanical properties of backfill.…”
Section: Introductionmentioning
confidence: 99%